2017
DOI: 10.1016/bs.acr.2017.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Animal Models to Study MicroRNA Function

Abstract: The discovery of the microRNAs, lin-4 and let-7 as critical mediators of normal development in Caenorhabditis elegans and their conservation throughout evolution has spearheaded research towards identifying novel roles of microRNAs in other cellular processes. To accurately elucidate these fundamental functions, especially in the context of an intact organism various microRNA transgenic models have been generated and evaluated. Transgenic C. elegans (worms), Drosophila melanogaster (flies), Danio rerio (zebraf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 254 publications
0
51
0
Order By: Relevance
“…Their main type of action is via (a) an inhibited translation and/or (b) by inducing the degradation of the mRNAs, known to be centrally involved in the epigenetic regulation of gene expression [70]. Micro-RNAs play a central role in cellular processes such as proliferation, differentiation, and apoptosis, which are known pathways affected in the development of chronic diseases including cancer [71]. Studies have shown that especially plant bioactives are able to affect miRNA expression which may partly explain their health-promoting properties documented in the development of various chronic inflammatory diseases [72][73][74].…”
Section: Epigeneticsmentioning
confidence: 99%
See 2 more Smart Citations
“…Their main type of action is via (a) an inhibited translation and/or (b) by inducing the degradation of the mRNAs, known to be centrally involved in the epigenetic regulation of gene expression [70]. Micro-RNAs play a central role in cellular processes such as proliferation, differentiation, and apoptosis, which are known pathways affected in the development of chronic diseases including cancer [71]. Studies have shown that especially plant bioactives are able to affect miRNA expression which may partly explain their health-promoting properties documented in the development of various chronic inflammatory diseases [72][73][74].…”
Section: Epigeneticsmentioning
confidence: 99%
“…Initial experiments identified lin-4 as the first miRNA being essential for the normal development of Ceanorhabditis elegans [75]. Drosophila melanogaster has also been successfully used to generate essential information on effects of miRNA, by establishing the Flp-FRT and GAL4-UAS systems, allowing to knock-in or knock-out specific miRNAs with particular functions in the fly [71]. The state-of-the-art technology CRISPR/Cas9 has been recently established in the context of miRNA research as miR-219 and miR-315 have been successfully knocked down in Drosophila melanogaster [76].…”
Section: Epigeneticsmentioning
confidence: 99%
See 1 more Smart Citation
“…MicroRNAs (miRNAs) are endogenous ∼ 22 nt RNAs that can play important regulatory roles in animals and plants by targeting mRNAs for translational repression [10]. The targeting of miRNAs could be a novel therapeutic approach, as evidenced by tumour regression in mouse models and initial promising data from clinical trials [11][12][13][14]. One recent study showed that miR-101, upregulated in DLBCL, suppressed DLBCL cell proliferation and facilitated apoptosis by inhibiting the expression of MEK1 [15], while miR-155, which is downregulated in DLBCL, suppressed DLBCL cell proliferation and facilitated apoptosis by upregulating SOCS3 expression to suppress the JAK-STAT3 signaling pathway [16].…”
Section: Introductionmentioning
confidence: 99%
“…Usually a single miRNA may target up to hundreds of protein-coding genes, and it is estimated that 74% to 92% of all protein-coding genes are conserved miRNA targets [3][4][5]. Many miRNAs are evolutionarily conserved and involved in growth, development, apoptosis, proliferation, and tumorigenesis of organisms [1,6].…”
Section: Introductionmentioning
confidence: 99%